Unknown environment exploration and mapping for an autonomous robot - Su, Marco Zhen Yi (Nanyang Technological University, 2020)
With autonomous ground vehicles getting more developed recently, it is being widely deployed across many industries to help reduce the workload of people. Many of these autonomous ground vehicles make use of Simultaneous Localization and Mapping (SLAM) technique to navigate about the environment. But there is a common problem of having to navigate an unknown environment without having a map of the place, it is unable to build a map and explore the environment accurately.